The BRICS and the future of global order - Stuenkel, Oliver (Lexington Books, 2015)
This book offers a history of the BRICS as a term and as an institution-a chronological narrative and analytical account of the BRICS concept from its inception in 2001 to the political grouping it is today. In addition, it analyzes what the rise of powers like Brazil, Russia, India, China, and South Africa means for the future of global order